PERAN MAGGOT SEBAGAI DETRITIVOR DALAM PENGOLAHAN LIMBAH TERNAK UNGGAS - Setiawan, Fauzi; Harlia, Ellin; Hidayati, Yuli Astuti (Unpad Press, 2023)
Processing of poultry livestock waste is carried out by composting, using microorganisms and maggot as decomposers and detritivores. The aim of the study was to determine the effect of using maggot as a detritivor in the bioconversion process of various poultry wastes on C/N ratio, pH value, temperature, media shrinkage water content, and maggot biomass. The research used a Completely Randomized Design (CRD) with three treatments, P1 = broiler chicken feces, P2 = laying hen feces and P3 = quail feces and repeated 6 times. The data obtained were analyzed using variance and to see differences between treatments, the Duncan test was carried out.The results showed a decrease in the C/N ratio after the initial decomposition respectively P1 = 25.68%; P2 = 21.13%; P3 = 11.83%. Conditions of pH (4.5 – 6) and temperature of 24 – 34°C during 21 days of decomposition, in all treatments did not show significant differences, and formed the same pattern, the water content of the media after 21 days of decomposition reached 19.05 - 25, 72%. Media shrinkage and maggot biomass in various treatments showed significant differences, P3 = quail feces produced the highest shrinkage (55.1%) and the highest maggot biomass was produced in P1 = broiler chicken feces (1.620 g)